2009
DOI: 10.1097/wnr.0b013e3283297d71
|View full text |Cite
|
Sign up to set email alerts
|

Joint activation of the supplementary motor area and presupplementary motor area during simultaneous motor and language functional MRI

Abstract: Recent research showed that the supplementary motor area (SMA) can be divided into a rostral pre-SMA, involved in higher-level processing and a caudal SMA proper, involved with motor execution. As surgical insults to the medial frontal lobes may cause variable neurological deficits and an incomplete understanding of structure-function relationships of the SMA exists, we sought to determine whether a common locus of functionality can be established using functional MRI. Results reveal a commonly activated regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…1) The SMA is functionally divided into 2 regions; the anterior portion of the SMA (pre-SMA) subserves language planning and the posterior portion is responsible for planning motor execution. 45 This functional subdivision while likely variable in its precise localization has been delineated by the VCA line (vertical commisure anterior line) drawn vertically from the anterior commisure. 46 It has been suggested that there is a graded functionality separating the pre-SMA and the SMA proper.…”
Section: Frontal Language Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…1) The SMA is functionally divided into 2 regions; the anterior portion of the SMA (pre-SMA) subserves language planning and the posterior portion is responsible for planning motor execution. 45 This functional subdivision while likely variable in its precise localization has been delineated by the VCA line (vertical commisure anterior line) drawn vertically from the anterior commisure. 46 It has been suggested that there is a graded functionality separating the pre-SMA and the SMA proper.…”
Section: Frontal Language Mappingmentioning
confidence: 99%
“…46 It has been suggested that there is a graded functionality separating the pre-SMA and the SMA proper. Peck et al 45 showed an area of common activation during both motor and language tasks, suggesting that there may be a region of the SMA that might carry a high probability of deficit if damaged. However, operative deficits relative to this region were not examined in this study.…”
Section: Frontal Language Mappingmentioning
confidence: 99%
“…16,17 The part related to motor planning is the caudal SMA proper and its function is intimately related to motor control. SMA localization is more difficult than the primary motor cortex (M1) on routine MRI examinations, as there is not a clear anatomical delineation.…”
Section: Motor Cortex and The Supplementary Motor Areamentioning
confidence: 99%
“…25 The SMA has been shown to be involved in temporal planning and organization of motor movements before execution, in addition to sequencing multiple movements. 26 Peck and colleagues 25,27 characterized the role of the SMA in patients with high-grade gliomas and their role in cortical reorganization. The study used fMRI to look at the BOLD hemodynamic responses in the primary motor and SMA of tumor patients.…”
Section: Supplementary Motor Areamentioning
confidence: 99%